Improving Students’ Reading Rate and Comprehension by using Timed Repeated Readings - Settiawan, Dodi (Journal of English and Arabic Language Teaching, 2013)
This study was carried out in a classroom action research design. It explored whether timed repeated readings could improve reading rate and comprehension. It examined the reading rate and comprehension at which the students of the Language Center achieved through timed repeated readings and also explained the factors that influence the changes of their reading rate and comprehension. Overall, the results showed that reading rate and comprehension could be improvedby using timed repeated readings and some factors that affected the improvements were identified.